Determination of Auroral Electrodynamic Parameters From AMPERE Field‐Aligned Current Measurements. Issue 4 (16th April 2021) - Robinson, R. M.; Zanetti, Larry; Anderson, Brian; Vines, Sarah; Gjerloev, Jesper
Abstract: We calculate high latitude electrodynamic parameters using global maps of field‐aligned currents from the Active Magnetosphere and Planetary Response Experiment (AMPERE). The model is based on previous studies that relate field‐aligned currents to auroral Pedersen and Hall conductances measured by incoherent scatter radar. The field‐aligned currents and conductances are used to solve for the electric potential at high latitudes from which electric fields are computed. The electric fields are then used with the conductances to calculate horizontal ionospheric currents. We validate the results by simulating the SuperMAG magnetic indices for 30 geomagnetically active days. The correlation coefficients between derived and actual magnetic indices were 0.68, 0.76, and 0.84 for the SMU, SML, and SME indices, respectively. We show examples of times when the simulations differ markedly from the measured indices and attribute them to either small‐scale, substorm‐related current structures or the effects of neutral winds. Overall, the performance of the model demonstrates that with few exceptions, auroral electrodynamic parameters can be accurately deduced from the global field‐aligned current distribution provided by AMPERE. Key Points: Relations between field‐aligned currents and ionospheric conductances are used to model electrical properties at high latitudes The spatial and temporal distribution of electric fields and currents can be calculated from maps of field‐aligned currents The currents derived from the model accurately replicate magnetic indices based on the SuperMAG global magnetometer network